Levels and enantiomeric ratios of alpha-HCH, oxychlordane, and PCB 149 in blubber of harbour seals (Phoca vitulina) and grey seals (Halichoerus grypus) from Iceland and further species - Klobes, U.; Vetter, W.; Luckas, B.; Skírnisson, K.; Plötz, Joachim (1998)
The chiral stationary phase beta-TBDM (35% heptakis(6-0-tert.-butyldimethylsily1-2-3-di-0-methyl)-beta-cyclodextrin in OV-1701) was applied to study the enantioenrichment of alpha-HCH, oxychlordane, and PCB 149 in blubber of two seal species from Iceland by gas chromatography with electron capture detection. The examined harbour seals (Phoca vitulina) and grey seals (Halichoerus grypus) showed alpha-HCH enantiomeric ratios (ER) >1. The ER of PCB 149 was comparable in the two species from Iceland but for oxychlordane ER <1 was observed in harbour seals while the oxychlordane ER in grey seals was >1. In blubber of Weddell seals (Leptonychotes weddelli) from the Antarctic we determined an alpha-HCH ER <1 which is in contrast to the Icelandic seal species and a sample from Lake Baikal.